2004
DOI: 10.1079/bjn20041209
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean dietary pattern among the population of the Balearic Islands

Abstract: The aim of the present study was to assess the prevalence of the Mediterranean dietary pattern (MDP) in the population of the Balearic Islands and socio-demographic and lifestyle factors that might determine adherence to the MDP. A cross-sectional nutritional survey was carried out in the Balearic Islands between 1999 and 2000. A random sample (n 1200) of the adult population (16-65 years) was interviewed. Dietary questionnaires incorporating questions related to socio-economic status, education level, lifesty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
72
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 20 publications
15
72
1
3
Order By: Relevance
“…In contrast to previous findings [14,31], success was lower among women, in spite of the fact that women are usually more motivated to respond to health messages focused on diet [14]. A reason that may explain this is that their baseline dietary patterns were closer to the intended dietary goals than those of men, and a healthier diet at baseline was a major predictor of not attaining the intended changes.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In contrast to previous findings [14,31], success was lower among women, in spite of the fact that women are usually more motivated to respond to health messages focused on diet [14]. A reason that may explain this is that their baseline dietary patterns were closer to the intended dietary goals than those of men, and a healthier diet at baseline was a major predictor of not attaining the intended changes.…”
Section: Discussioncontrasting
confidence: 87%
“…Consistently with the literature, failure to meet the dietary goals was usually found among older participants [31,35], which may be explained because our participants had deeply rooted dietary habits and they were already fairly adherent to the MeDiet pattern at baseline [8,26].…”
Section: Discussionsupporting
confidence: 86%
“…Several epidemiological studies reported a direct association between diet quality and healthy lifestyle variables (Ruidavets et al, 2004;Thiele et al, 2004;Tur et al, 2004). In the present population, participants with a high adherence to low-energy density diets showed a trend towards a healthier lifestyle characterized through a higher degree of physical activity during leisure time, lower prevalence of smoking, sedentary lifestyle and alcohol consumption.…”
Section: Discussionmentioning
confidence: 54%
“…Recent nutritional surveys carried out in Spain also confirmed a progressive departure from the traditional Mediterranean diet towards a Western dietary pattern, mainly in young generations (5)(6)(7)(8)(9)(10)(11) . Because there is evidence that nutritional behaviours track from adolescence into adulthood, the promotion of healthy nutrition during adolescence has the potential to confer significant long-term health benefits (1) .…”
mentioning
confidence: 85%